The Immigrant Advantage in Adolescent Educational Expectations. Issue 3 (September 2016) - Feliciano, Cynthia; Lanuza, Yader R.
Previous research has shown uniquely high expectations among children of immigrants. However, existing studies have not focused on why children of immigrants have an expectations advantage over their native-born counterparts or if this has changed over time. This study shows that an immigrant advantage in graduate school expectations persists among adolescent children of immigrants today. Regression analyses reveal that this advantage is largely explained by higher parental expectations, greater interest in school, and foreign language use in early childhood. We argue that these factors can be conceptualized as forms of cultural capital stemming from unique aspects of the immigrant experience that are common across immigrant families.